PERBANDINGAN AKURASI CAPM DAN APT MENGGUNAKAN UJI MAD DALAM MEMPREDIKSI RETURN SAHAM FARMASI TERDAFTAR DI BEI PERIODE FEBRUARI 2020- DESEMBER 2022 - Novita Sari; Immas Nurhayati; Renea Shinta Aminda (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This study aims to determine the accuracy of the CAPM and APT models to predict pharmaceutical stock returns listed on the IDX in 2020-2022. This research uses comparative descriptive with a quantitative approach. The data used is secondary data with purposive sampling technique in the form of data from the Indonesia Stock Exchange (IDX), namely data on the Composite Stock Price Index (IHSG), in addition to collecting secondary data from Yahoo.finance, namely data on Stock Prices. as well as secondary data on Economic Factors through Bank Indonesia (BI) and the Central Statistics Agency (BPS), namely data on Inflation, Exchange Rates, Money Supply and Interest Rates. This research technique uses an independent two-sample test. The accuracy of the two models is measured using the Mean Absolute Deviation test to predict stock returns. the results show that the Capital Assets pricing Model is more accurate than Arbitrage Pricing Theory.